2003
DOI: 10.1007/s00427-003-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

A genomewide survey of developmentally relevant genes in Ciona intestinalis

Abstract: Homeobox-containing genes play crucial roles in various developmental processes, including body-plan specification, pattern formation and cell-type specification. The present study searched the draft genome sequence and cDNA/EST database of the basal chordate Ciona intestinalis to identify 83 homeobox-containing genes in this animal. This number of homeobox genes in the Ciona genome is smaller than that in the Caenorhabditis elegans, Drosophila melanogaster, human and mouse genomes. Of the 83 genes, 76 have po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 45 publications
4
89
1
Order By: Relevance
“…6). At present, it is difficult to decide when the change in the genomic structure of CUX/CASP or the gain and loss of SATB and COMPASS took place due to the limited genome sequence resources in the lower chordates, although previous study reported that genes encoding CUX, COMPASS and SATB were not found in the genome of Ciona intestinalis (Wada et al, 2003). Future genome sequencing of lower chordates will resolve this issue.…”
Section: A New Model For the Evolution Of Cut Class Homeobox Genes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…6). At present, it is difficult to decide when the change in the genomic structure of CUX/CASP or the gain and loss of SATB and COMPASS took place due to the limited genome sequence resources in the lower chordates, although previous study reported that genes encoding CUX, COMPASS and SATB were not found in the genome of Ciona intestinalis (Wada et al, 2003). Future genome sequencing of lower chordates will resolve this issue.…”
Section: A New Model For the Evolution Of Cut Class Homeobox Genes Inmentioning
confidence: 99%
“…Recently, the genome resources of non-vertebrate deuterostomes have become available, including ascidian Ciona intestinalis (http:// genome.jgi-psf.org/Cioin2/Cioin2.home.html), sea urchin Strongylocentrotus purpuratus (http://www.ncbi.nlm.nih.gov/genome/guide/sea_urchin/) and amphioxus Branchiostoma floridae (http://genome.jgi-psf.org/Brafl1/Brafl1.home.html). In the genome of C. intestinalis, however, only ONECUT has been identified as CUT class homeobox genes (Wada et al, 2003) and in the S. purpuratus genome, two members, ONECUT and CUX, have been reported (Howard-Ashby et al, 2006), raising a possibility that other members of CUT class homeobox genes may have been lost in these animal species. Therefore, the genome resource of amphioxus is particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been observed that motoneurons may still form in isolated A4.1 explants (Okada et al, 1997). We used two motoneuron markers, Ci-ChAT, which encodes cholinergic acetyltransferase (Takamura et al, 2002;Yoshida et al, 2004), and the Ciona homologue of HB9 and MNR2 genes, which play a crucial role in motoneuron specification in other systems, and of which there is one representative in the Ciona genome, Ci-HB9/MNX (Broihier and Skeath, 2002;Odden et al, 2002;Shirasaki and Pfaff, 2002;Wada et al, 2003). Expression of these motoneuron markers was completely dependent on an intact Nodal signalling pathway ( Fig.…”
Section: A Collection Of Neural Plate Markers To Investigate Neural Pmentioning
confidence: 99%
“…In previous studies Wada et al, 2003), we identified whole gene sets for bHLH factors and homeobox transcription factors encoded in the Ciona intestinalis genome, the draft sequence of which we recently determined (Dehal et al, 2002). We comprehensively examined their expression patterns during embryogenesis, and thereby found that five bHLH genes and one homeobox gene were expressed predominantly in mesenchymal cells.…”
Section: Genes Expressed In Presumptive Mesenchymal Cells Of Early CImentioning
confidence: 99%